Factors that Influence Canadian Generalist and Physical Education Specialist Elementary School Teachers’ Practices in Physical Education: A Qualitative Study - Truelove, Stephanie; Bruijns, Brianne A.; Johnson, Andrew M.; Burke, Shauna M.; Tucker, Patricia (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
Interviews were conducted with 16 elementary school teachers across Canada (eight generalists and eight physical education [PE] specialists) to explore their experiences when instructing PE. Questions were phrased to encourage exploration of the perspectives of generalists and specialists, with a particular focus on teaching philosophy, barriers faced while instructing PE, facilitators and resources that enhance PE instruction, and the teachers’ self-efficacy when teaching PE. Generalists noted perceived lack of time, inadequate facilities and equipment, insufficient training, lack of knowledge, and low self-efficacy as barriers. Conversely, specialists noted that their advanced training, professional development opportunities, high self-efficacy, and technology use positively supported their teaching practices.